Analisis Sistem Informasi Pelayanan Publik pada Sistem Komputerisasi Tenaga Kerja Luar Negeri (SISKOTKLN) di Kabupaten Kepahiang - Anjalika, Annisa Octa; Adriadi, Rekho; Darmi, Titi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
One of the embodiment of e-government spirit is an SISKOTKLN. Kepahiang is one of the districts in Bengkulu who already used Public Service Information System in SISKOTKLN program. This study aims to analyze Public Service Information System in SISKOTKLN programs in Kepahiang District. The method of this research is descriptive qualitative. Data collection techniques by direct observation, in-depths interviews, and documentation. The results of this study indicate that from the System Quality, Service Quality, User Satisfaction and Net Benefit user used in this study indicates that SISKOTKLN has run well and has achieved its goal that is to make administrative services of the TKI placement properly, quickly, easily and efficiently. The application of SISKOTKLN also has a positive impact on the service and performance of the organization. But for indicator of Information Quality is found that SISKOTKLN is not socialized directly to the community.